Head impact velocities in FIS World Cup snowboarders and freestyle skiers: Do real-life impacts exceed helmet testing standards? - Steenstrup, S. E.; Mok, K.-M.; McIntosh, A. S.; Bahr, R.; Krosshaug, T. (British Journal of Sports Medicine, 2018)
Introduction: Prior to the 2013-2014 season, the International Ski Federation (FIS) increased the helmet testing speed from a minimum requirement of 5.4 to 6.8 m/s for alpine downhill, super-G and giant slalom and for freestyle ski cross, but not for the other freestyle disciplines or snowboarding. Whether this increased testing speed reflects impact velocities in real head injury situations on snow is unclear. We therefore investigated the injury mechanisms and gross head impact biomechanics in four real head injury situations among World Cup (WC) snowboard and freestyle athletes and compared these with helmet homologation laboratory test requirements. The helmets in the four cases complied with at least European Standards (EN) 1077 (Class B) or American Society for Testing and Materials (ASTM) F2040. Methods: We analysed four head injury videos from the FIS Injury Surveillance System throughout eight WC seasons (2006-2014) in detail. We used motion analysis software to digitize the helmet`s trajectory and estimated the head`s kinematics in two dimensions, including directly preimpact and postimpact. Results: All four impacts were to the occiput. In the four cases, the normal-to-slope preimpact velocity ranged from 7.0(±SD 0.2) m/s to 10.5±0.5 m/s and the normal-to-slope velocity change ranged from 8.4±0.6 m/s to 11.7±0.7 m/s. The sagittal plane helmet angular velocity estimates indicated a large change in angular velocity (25.0±2.9 rad/s to 49.1±0.3 rad/s). Conclusion: The estimated normal-to-slope preimpact velocity was higher than the current strictest helmet testing rule of 6.8 m/s in all four cases.